Amylolytic Enzyme Production Using Agricultural Residue - Pathak, Anupama P.; Sarsar, Mayuri S.; Gavali, Joice T.; Sonwane, Rohini G. (International Journal For Research In Agricultural And Food Science, 2016)
Four different fungal cultures i.e. Aspergillus niger (MTCC 1781), Aspergillus fumigatus (MTCC 2557), Aspergillus oryzae (MTCC 654), Aspergillus paraciticus (MTCC 411) were collected from culture collection section of School of Life Sciences, SRTMU, Nanded, Maharashtra, India. Solid State Fermentation (SSF) was carried out using mixture of four different substrate namely Wheat bran, Banana peel, Pineapple peel and Pomegranate peel. After production by four fungal cultures using this substrate it was found that A.paraciticus showed maximum production of amylase (41U/ml) as compare to other cultures.